Effect of C/N ratio on the denitrifying enzymes activity and global warming potential - Yin Zhou; Peifang Wang; Bin Hu; Dingxin Li; Tianming Zheng; Ting Chen (Desalination and Water Treatment)
The greenhouse gases generated in the wastewater treatment process based on heterotrophic denitrification technology have become a dilemma between water environment protection and carbon emission reduction. Therefore, balancing the removal of nitrate pollutants and greenhouse gas emissions has become a key issue in ''green denitrification''. Based on the insufficient research of previous studies on C/N and global warming potential (GWP) in denitrification systems, this study constructed a series of batch experiments with different initial C/N to analyze their impact on the denitrifying enzymes specific activity concentration and the GWP caused by GHGs emissions. This study indicates that when the initial C/N is below 6.82, it leads to a decrease in the nitrous oxide reductase specific activity concentration by 0.11∼12.45 %, but an increase in the nitric oxide reductase specific activity concentration by 5.96∼22.01 %. In addition, when the initial C/N was between 2.34 ∼ 6.82, the GWP caused by every complete reduction of 1 mg NO-3-N has a better cost-effectiveness, with 0.09 ∼ 0.13 mmol CO2-eq/mg NO-3-N. Overall, the results of the study provide a reference for balancing the nitrate removal and the GWP caused by GHGs emission in wastewater treatment.